The pro‐ or anti‐apoptotic function of NF‐κB is determined by the nature of the apoptotic stimulus - Kaltschmidt, Barbara; Hofmann, Thomas G.; Dröge, Wulf (EJB, 2003)
To test whether the behaviour of transcription factor NF‐κB as a promoter or antagonist of apoptosis depends on the apoptotic stimulus, we determined the influence of NF‐κB on cell killing elicited by a variety of inducers within a given cell type.